2022
DOI: 10.1007/s41062-022-00826-8
|View full text |Cite
|
Sign up to set email alerts
|

Developing machine learning model to estimate the shear capacity for RC beams with stirrups using standard building codes

Abstract: Developing machine learning model to estimate the shear capacity for RC beams with stirrups using standard building codes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…To date, ML approaches have been used for strength predictions of concrete structures, capitalizing on the extensive amount of experimental data and low accuracy of traditional mechanical prediction models, especially for shear problems [26][27][28][29][30][31][32][33][34]. The current investigations have demonstrated that the data-driven ML approaches could provide strength predictions with significantly high accuracy compared with the design provisions.…”
Section: Introductionmentioning
confidence: 91%
“…To date, ML approaches have been used for strength predictions of concrete structures, capitalizing on the extensive amount of experimental data and low accuracy of traditional mechanical prediction models, especially for shear problems [26][27][28][29][30][31][32][33][34]. The current investigations have demonstrated that the data-driven ML approaches could provide strength predictions with significantly high accuracy compared with the design provisions.…”
Section: Introductionmentioning
confidence: 91%
“…According to the results of the study findings, the XGBoost model performs well compared to other ML techniques and existing guidelines. Uddin et al 27 used ANN, RF, GEP, and GBDT to predict the shear strength of RC beams. The performance of GBDT algorithm was good compared to ANN, RF and GEP algorithms.…”
Section: Introductionmentioning
confidence: 99%